Untersuchung der Wechselwirkung von NO und Ruß in laminaren, rußenden Vormischflammen - Ebersohl, Nicole (KIT Scientific Publishing, 2015)
Emission limits are being steadily tightened. This requires an ever increasing reduction of combustion generated pollutants. This book focuses on soot and NO and their heterogeneous interactions. With the help of laser spectroscopic methods and mathematical modeling of flames, a heterogeneous reaction mechanism for surface reactions can be validated and a significant influence on precursor reactions of soot formation can be shown.